Role of Satisfaction in The Influence of Destination Image on Tourist Attitudinal Loyalty - Luh Putu Kartini; I Putu Utama; Amirosa Ria Satiadji (Politeknik Pariwisata Bali, 2022)
Tourist loyalty is very important for tourist destinations as it showing commitment and willingness to recommend to other so the business processes in destination can continue to grow. This research aims to analyze the role of satisfaction in the influence of destination image through attitudinal loyalty in Medana Village, Tanjung – North Lombok from tourist’s perspective. The data collection of this research was carried out by purposive sampling method through the distribution of questionnaires, observations, literature studies and secondary data, also interviews. Analysis of the data used is path analysis using SEM (Structural Equation Modeling) with mediating effects and tested with AMOS and Sobel-test. The results stated that satisfaction is able to mediate the effect of destination image on attitude loyalty. However, there are still improvements needed to increase tourist satisfaction, such as develop a customer-centric strategy, formulate transformative services and gaining support from the association/industry.